The Serum Total and Lipid-Bound Sialic Acid with Hematological-Biochemical Parameter Levels in Dogs with Dirofilariosis - Kesici, Hasan; Değer, Yeter; Oguz, Bekir; Özdek, Uğur (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study was planned to investigate the potential changes in the levels of serum total sialic acid (TSA), lipid-bound sialic acid (LSA) and hematological-biochemical parameters in the dogs naturally infected by Dirofilaria immitis. The patient group included the 7 dogs clinically and parasitologically (Modified Knott and PCR) diagnosed with Dirofilaria immitis while 7 healthy dogs were assigned as the control group. The biochemical parameters, blood gas parameters and hematological parameters were tested in the blood samples taken properly according to the guidelines from all the study animals using modular auto-analyser, blood gas analyser and automated blood count devices, respectively. Serum TSA and LSA levels were measured spectrophotometrically using Sydow and Katapodis methods, respectively. Compared with the healthy group, the dogs diagnosed with dirofilariosis were found to have significantly increased levels of serum troponin, triglycerides, VLDL, LDL, BUN, urea and creatinine and enzymatic activities of CK-MB, ALT, AST, ALP and LDH, and statistically significantly decreased levels of cholesterol and HDL (p<0.05). The increases in levels of total protein and total bilirubin, and enzymatic activity of CK were found statistically insignificant (p>0.05). A significantly decreased level of RBC and a significantly increased level of WBC was determined in the dogs with dirofilariosis (p<0.05). The decreases in the levels of Hct and Hb were found statistically insignificant (p>0.05). The differential blood count test of the dogs with dirofilariosis indicated statistically significantly increased eosinophil count (p<0.05). The increases in the neutrophil and basophil counts, and the decreases in the lymphocyte and monocyte counts were detected to be statistically insignificant (p>0.05). In the dogs with dirofilariosis, the decreases in the levels of pCO2, HCO3 and BE as the venous blood gas parameters were detected to be statistically significant (p<0.05). The decreases in the levels of pH and pO2 were determined to be insignificant (p>0.05). The levels of serum TSA and LSA of the dogs with dirofilariosis were found statistically significantly higher than the healthy group (p<0.05). As a conclusion, statistically significant differences were identified between the dogs with dirofilariosis and healthy dogs in terms of sialic acid levels and certain biochemical, venous blood gas and hematological parameters. On the other hand, the present study is the first to investigate the serum sialic acid levels in the dogs with dirofilariosis.